The Phenomenon of Psychological Operations as a Concept and Discourse (Based on Security Linguistic Cultures of the NATO and the Russian Federation) - Лариса Компанцева (Психолінгвістика, 2020)
Objective. The purpose of this paper is to present an argument for the status of the phenomenon of psychological operations as a concept and discourse.